The catalan Queralt-Timor lineage and its relationship with the Order of the Temple (12th-14th centuries) - Fuguet Sans, Joan (2021)
The commandery of the Temple of Barbera (Tarragona) was one of the leading ones of the Crown of Aragon, thanks in part to the collaboration of one of the most notable ‘Templar families’: Queralt-Timor of Santa Coloma. From the beginning of this commandery in the last decades of the twelfth century, they had been its main benefactors and, later on, provided the Militia with knights of the first rank (Pere II de Queralt, Jaume de Timor, Arnau de Timor, Dalmau de Timor...). They were all professional warriors and took an active part in the conquests which the monarchy carried out in the thirteenth century. But in addition, the Queralt family developed a continuous matrimonial policy which linked it by marriage to the different main lineages of the country, also connected to the Temple: Castellnou, Anglesola, Rocaberti… This article is particularly interested in the life and activities of these individuals with the intention of re-evaluating their contribution and giving them the place they deserve in the history of the Temple.   Bibliography Printed sources ALBON, Marquis d' – Cartulaire Général de l'Orde du Temple 1119?-1150. París: Librairie Ancienne, Honoré Champion, Éditeur, 1913. ALTISENT, Agustí – Diplomatari de Santa Maria de Poblet, vol I, anys 960-1177. Barcelona: Abadia de Poblet; Departament de Cultura de la Generalitat de Catalunya, 1993. BOFARULL I MASCARÓ, Pròsper de – Colección de documentos inéditos del Archivo General de la Corona de Aragón. 41 vols., Barcelona: L. Benaiges - José Eusebio Monfort, 1847-1910. BRUGUERA, Jordi (ed.) – Llibre dels Fets del rei En Jaume. 2 vols. Barcelona: Editorial Barcino, 1991. FINKE, Heinrich – Papsttum und Untergang des Templerordens, II Band: Quellen, Münster, 1907. FINKE, Heinrich – Acta Aragonensia: quellen zur Deutschen, Italienischen, Französischen, Spanischen, zur Kirchenund Kulturgeschichte aus der Diplomatischen Korrespondenz Jaymes II: 1291-1327. Berlin, Leipzig: W. Rothschild, 1908. GONZALVO I BOU, Gener – Les constitucions de Pau i Treva de Catalunya (segles XI i XIII). Barcelona: Departament de Justícia, Generalitat de Catalunya, 1994. PALOU I MIQUEL, Hug – Els libri notularum de Santa Coloma de Queralt (1240-1262). 2 vols. Barcelona: Fundació Noguera, 2009. SANS I TRAVÉ, Josep M. – Col·lecció Diplomàtica de la casa del Temple de Barberà. Barcelona: Departament de Justícia, Generalitat de Catalunya, 1997. TRETON, Rodrigue – Diplomatari del Masdéu, I-V, Barcelona: Fundació Noguera, Barcelona, 2010.   Studies ALTISENT, Agustí – “Un poble de la Catalunya Nova els segles XI i XII. L'Espluga de Francolí de 1079 a 1200”. Anuario de Estudios Medievales 3 (1966), pp. 131-213. ALVIRA, Martín – “Destruir aquells qui reneguen lo nom de Jhesucrist. El obispo de Barcelona Berenguer de Palou (1212-1241)”. in Ayala Martínez, Carlos de; Palacios Ontalva, J. Santiago (eds.) – Hombres de religión y guerra. Madrid: Sílex ediciones, 2018, pp. 373-388. AYALA MARTÍNEZ, Carlos de – “Guerra y Órdenes Militares en la Edad Media: Balance y perspectivas de estudio”. in FERNANDES, Isabel Cristina (coord.) - Entre Deus e o Rei. O mundo das ordens militares. Palmela: Município de Palmela- GEsOS, 2018, vol. I, pp. 179-188. BENET I CLARÀ, Albert – La família Gurb-Queralt (956-1276): senyors de Sallent, Oló, Avinyó, Gurb, Manlleu, Voltregà, Queralt i Santa Coloma de Queralt. Sallent: Institut d’Arqueologia, Història i Ciències Naturals, 1993. BONET DONATO, María – “Identidad de las hospitalarias en la Corona de Aragón”. Memoria y Civilización. Anuario de Historia 17 (2014), pp. 43-87. BULST-THIELE, M. Louise – Sacrae domus militiae Templi Hierosolymitani magistri, Untersuchungen zur Geschichte des Templerordens, 1118-1314. Göttingen: Vandenhoeck und Ruprecht, 1974. BURGTORF, Jochen – The Central Convent of Hospitallers and Templars: History, Organization, and Personnel (1099/1120-1310). Leiden: Brill, 2008. BUSQUETA I RIU, Joan – “Notícia sobre els Anglesola a la ciutat de Lleida”. XXXIX Jornada de Treball. Anglesola: Grup de Recerques de les Terres de Ponent, 2010, pp. 358-368. CARRAZ, Damien – “Memoire lignagère et archives monastiques: les Bourbouton et la commanderie de Richerenches”. in AURELL, Martin (ed.) – Convaincre et persuader: communication et propagande au XIIè et XIIIè siècles. Poitiers: Université de Poitiers, 2007, pp. 465-502. CARRAZ, Damien – “L’affiliation des laics aux commanderies templières et hospitalières de la basse vallée du Rhône (XIIe-XIIIe siècles)”. in LUTTRELL, Anthony; TOMMASI, Francesco (eds.) – Religiones militares: contributi alla storia degli Ordini Religioso-militari nel medioevo. Città di Castello: Selecta, 2008, pp. 171-190. CARRAZ, Damien – Damien – “Donation”. in Bériou, Nicole; Josserand, Philippe (eds.) - Prier et combatre. Dictionnaire européen des ordres militaires au Moyen Âge. Paris: Fayard, 2009. CHEVALIER, Marie-Anna (dir.) – Ordres militaires et territorialité au Moyen Âge entre Orient et Occident. París: Geuthner, 2020, pp. 271-310. CINGOLANI, Stefano Maria – Pere el Gran. Vida, actes, paraula. Barcelona: Editorial Base, 2010. CID PRIEGO, Carlos – “La escultura de la portada de la iglesia de Santa María de Belloc de Santa Coloma de Queralt”. Boletín Arqueológico 52 (1952), pp. 137-176. CID PRIEGO, Carlos – La iglesia de Santa María de Belloc en Santa Coloma de Queralt. Santa Coloma de Queralt: Ayuntamiento de Santa Coloma de Queralt, 1954. CLAVERIE, Pierre-Vincent – “La contribution des templiers de Catalogne à la defense de la Syrie franque (1290-1310)”. in Vermeulen, U.; Van Steenbergen, J. (eds.) – Egipt and Syria in the Fatimid, Ayyubid and Mamluk Eras III. Leuven: Peeters, 2001, pp. 171-192. (Proceedings of the 6th, 7th and 8th International Colloquium organized at the Katholieke Universiteit Leuven in May 1997, 1998 and 1999). CLAVERIE, Pierre-Vincent – “Un moment clé de l’histoire du Royaume de Majorque: la fin de la vicomté de Castelnou (1321-1369)”. e-Spania [En línea] 29 (Consultado en 5 Noviembre 2020). Disponible en https://doi.org/10.4000/e-spania.27099. CONILL, Miquel – Heroica vida y exemplares virtudes del Venerable Doctor D. Francisco de Queralt. Cervera: Impremta de la Universitat, 1736. CORTADA, Juan – El templario y la villana. Crónica del siglo XIV. Barcelona:  Imprenta de Brusi, 1840. COSTA I PARETAS, M. Mercè – “La família Queralt i Santes Creus”. in I Col·loqui d’Història del Monaquisme Català. Santes Creus: Publicacions de l'Arxiu Bibliogràfic de Santes Creus, Vol. I, 1966, pp. 92-109. CURZI, Gaetano – La pittura dei Templari. Milán: Silvana Editoriale, 2002. DEMURGER, Alain – “L'aristocrazia laica e gli ordini militari in Francia nel Duecento: l'esempio della Bassa Borgogna”. in Coli, Enzo; De Marco, Maria; Tommasi, Francesco (eds.) – Militia Sacra. Gli ordini militari tra Europa e Terrasanta. Perugia: Società Editrice S. Bevignate, 1994, pp. 55-84. DEMURGER, Alain – Les Templiers. Une chevalerie chrétienne au Moyen Âge. París: Seuil, 2005. DÍAZ MANTECA, Eugeni – “La venda del castell de Culla al Temple: un procés llarg i dificultós (1303-1388)”. in Estudis recollits en el 750è aniversari de la carta de població (1244-1994). Culla: Comissió de Cultura per al 75è aniversari de la carta de població, vol. 2, 1994, pp. 451-481. DURAN I SANPERE, Agustí – Els retaules de pedra. Vol. I. Monumenta Cataloniae. Barcelona: Ed. Alpha, 1932. ESPAÑOL BERTRAN, Francesca – L’arquitectura religiosa romànica a la Conca de Barberà i Segarra tarragonina. Montblanc: Centre d’Estudis de la Conca de Barberà, 1991. FELIU I MONTFORT, Gaspar – “La baronia d'Utxafava (1283-1422)”.  Acta Mediaevalia 25 (2003-2004), pp. 257-276. FERRÉS I ARDERIU, Pere – “Un jove romàntic Ramon Picó i Campanar”.  Anuari Verdaguer 12 (2004), pp. 11-80. FLUVIÀ I ESCORÇA, Armand de – “Rocabertí”. in Gran Enciclopèdia Catalana, 12, Barcelona, 1978, pp. 653-658. FOREY, Alan J. – The Templars in the ‘Corona de Aragón’. Londres: Oxford University Press, 1973. FOREY, Alan J. – “Recruitment to the Military Order (twelft to mid-fourteenth centuries)”. Viator 17 (1986), pp. 139-171. FOREY, Alan J. – “Women and the Military Orders in the twelfth and thirteenth centuries”.  Studia Monastica 29 (1987), pp. 63-92. FOREY, Alan J. – “Letters of the last Two Templars Masters”. Nottingham Medieval Studies 45 (2001), pp. 166-167. FOREY, Alan J. – The fall of the Templars in the crown of Aragon. Ashgate: Aldershot, 2001. FOREY, Alan J. – “A Templar Lordship in Northern Valencia”. in CZAJA, Roman; SARNOWSKY, Jürgen – Selbstbild und Selbstverständnis der Geistlichen Ritterorden. Torun: Wydawnictwo Universytetu Mikolaja Kopernika, 2007, pp. 59-68. FOREY, Alan J. – “Aragonese templars in the Holy Land and Cyprus in the late thirteenth and early fourteenth centuries”. in Fernandes, Isabel Cristina F. – As Ordens Militares e as Ordens de Cavalaria. Entre o Occidente e o Oriente. Actas do V Encontro sobre Ordens Militares, 15 a 18 de Fevereiro de 2006. Palmela: Câmara Municipal de Palmela-GEsOS, 2009, pp. 451- 461. FOREY, Alan J. – “The Careers of Templar and Hospitaller Office-Holders in Western Europe during the Twelfth and Thirteenth Centuries”. in JOSSERAND, Philippe; OLIVEIRA, Luís F.; CARRAZ, Damien – Élites et ordres militaires au Moyen Âge, Madrid: Casa de Velásquez, 2015, pp. 201-214. FORT I COGUL, Eufemià – “Pere de Queralt, insigne collaborador de Pere el Gran i egregi amic de Santes Creus”. Boletín Arqueológico 93-96 (1966), pp. 129-139. FUGUET SANS, Joan– “L'arquitectura dels templers al Camp de Tarragona i la seva aportació als orígens del “gòtic català”. XXXV Assemblea Intercomarcal d’Estudiosos de Catalunya. Valls 24, 25 i 26 de novembre de 1989. Estudis Vallencs 28. Catalunya: Institut d’Estudis Vallencs, 1989, pp. 369-401. FUGUET SANS, Joan – “Santuaris marians de l'Orde del Temple a Catalunya". Afers, fulls de recerca i pensament 10 (1990), pp. 419-433. FUGUET SANS, Joan – L’arquitectura dels templers a Catalunya. Barcelona: Rafael Dalmau Ed., 1995. FUGUET Sans, Joan – “Consideracions sobre l’ús de la creu en l’Orde del Temple”. in El temps sota control, Homenatge a F. Xavier Ricomà Vendrell. Tarragona: Diputació de Tarragona, 1997, pp. 295-308. FUGUET SANS, Joan – “Contribució a l'estudi dels orígens del gòtic meridional: influència de l'arquitectura popular en les construccions templeres i cistercenques catalanes”. in Miscel·lània en homenatge a Joan Ainaud de Lasarte. Barcelona: Museu Nacional d’Art de Catalunya-Institut d’Estudis Catalans- Publicacions de l'Abadia de Montserrat, 1998, vol. I, pp. 225-236. FUGUET SANS, Joan – Templers i hospitalers, II. Guia de les terres de l’Ebre i dels castells templers del Baix Maestrat. Barcelona: Rafael Dalmau Ed., 1998. FUGUET SANS, Joan – “Les esglésies amb arcs de diafragma de la Catalunya Nova”.  in Bracons, Josep; Freixas, Pere (coords.) – L'Art Gòtic a Catalunya. Arquitectura I. Catedrals, monestirs i altres edificis religiosos. Barcelona: Enciclopèdia Catalana, 2002, vol. I, pp. 152-159. FUGUET SANS, Joan – Templers i Hospitalers, IV. Guia de la Catalunya Vella, el Penedès, els comtats del Rosselló i Mallorca. Barcelona: Rafael Dalmau Ed., 2005. FUGUET SANS, Joan – “Any 1307, un capítol provincial dels templers catalano aragonesos a Sant Francesc de Montblanc”. Foradot 52 (2009), pp. 20-22. FUGUET SANS, Joan – “Historia y patrimonio artístico de los templarios en Cataluña”. Cuadernos del Centro de Estudios de Monzón y Cinca Medio 41 (2015), pp. 139-181. FUGUET SANS, Joan; ARTIGAU MIRALLES, Montserrat; FRANCH PAGÈS, Silvia – “La galeria del castell templer de Corbera d’Ebre”. Unicum 2 (2003), pp. 4-15. FUGUET SANS, Joan; PLAZA ARQUÉ, Carme – “L’ordre de l’Hôpital de Saint-Jean de Jérusalem dans les territoires pyrénéens du nord de la Catalogne et de l’Aragon”. in Fuguet Sans, Joan; Plaza Arqué, Carme; Hofbauerová, Vera – Els Queralt a Santa Coloma, arquitectura, art i vida. Santa Coloma: Ajuntament de Santa Coloma, 2010. FUGUET SANS, Joan; PLAZA ARQUÉ, Carme – “Culto a los santos y lucha contra el Islam en las Órdenes Militares de la Corona catalano-aragonesa”. in Carraz, Damien; Dehoux, Esther (dirs.) – Images et ornements autour des Ordres Militaires au Moyen Âge. Toulouse: Presses universitaires du Midi, 2016, pp. 36-38. IGLESIES FORT, Josep – El fogatge de 1553. Estudi i transcripció. Barcelona: Fundació Vives Casajuana, 1979-1980. JASPERT, Nikolas – “Capta est Dertosa, clavis cristianorum: Tortosa and the Crusades”. in PHILLIPS, Jonathan (ed.) – The second crusade - scope and consequences. Manchester: Manchester University Press, 2001, pp. 90-110. JASPERT, Nikolas – “The election of Arnau de Torroja as ninth Master of the Knights Templar (1180): an enigmatic decision reconsidered”. in Fernandes, Isabel Cristina (coord.) – As Ordens Militares e as Ordens de Cavalaria. Entre o Ocidente e o Oriente. Actas do V Encontro sobre Ordens Militares, 15 a 18 de Fevereiro de 2006. Palmela: Câmara Municipal de Palmela-GEsOS, 2009, pp. 371-398. JOSSERAND, Philippe – Église et pouvoir dans la Peninsule Ibérique. Les Ordres Militaires dans le Royaume de Castille (1252-1369). Madrid: Casa de Velázquez, 2004. LAVEDAN, Pierre – L'architecture gothique religieuse en Catalogne, Valence et Baléares. París: Henri Laurens ed., 1935. LIAÑO MARTÍNEZ, Emma – “Las iglesias góticas de Santa Coloma de Queralt”.  Aplec de Treballs 2 (1980), pp. 21-50. MAGNOU, Élisabeth – “Oblature, classe chevalesque et servage dans les maisons méridionales du Temple au XIIe siècle”.  Annales du Midi 73 (1961), pp. 377-397. MARCA, Petrus de – Marca Hispanica sive limes Hispanicus. París: 1688. MARTINELL BRUNET, Cèsar – El monestir de Poblet. Barcelona: Ed. Barcino, 1927. MARTINELL BRUNET, Cèsar – “Arquitectura mercedaria”. Cuadernos de Arqueología e Historia de la Ciudad 8 (1965), pp. 59-71. MAS I VIVES, Joan – El teatre a Mallorca a l’època romàntica. Barcelona: Publicacions de l’Abadia de Montserrat, 1986. MASIÁ DE ROS, Ángeles – Relación castellano-aragonesa desde Jaime II a Pedro el Ceremonioso. Madrid: CSIC, 1994, 2 vols. MIRAMON, Charles de – Les “donnés” au Moyen Âge: une forme de vie religieuse laïque, v. 1180 - v. 1500. Paris: Les Editions du Cerf, 1999. MIRET I SANS, Joaquim – Les cases de templers y hospitalers en Catalunya. Barcelona: Casa Provincial de Caritat, 1910. MORERA I LLAURADÓ, Emili – Tarragona cristiana, I. Tarragona: Establecimiento tipográfico de F. Arís e Hijo, 1897. MORERA I LLAURADÓ, Emili – “Provincia de Tarragona”. in Carreras Candi, Francesc (dir) - Geografia General de Catalunya. Barcelona: Establiment Editorial de Albert Martín, s. d. [1909?]. NICHOLSON, Helen – "Women in Templar and Hospitaller Commanderies". in Luttrell, Anthony; Pressouyre, Léon (dirs.) – La Commanderie, institution des ordres militaires dans l'Occident médiéval. París: Comité des travaux historiques et scientifiques, 2002, pp. 125-134. PAGAROLAS SABATER, Laureà – Els templers de les Terres de l’Ebre (Tortosa). De Jaume I fins a l’abolició de l’Orde (1213-1312). 2 vols. Tarragona: Diputació de Tarragona, 1998. PIÉ FAIDELLA, Joan – Relación histórica del santuario de Paret Delgada. Tarragona: Tip. de F. Arís e Hijo, 1896. PLAZA ARQUÉ, Carme – "El Promasó (Masó)”. Butlletí Interior. Societat d'Onomàstica 37 (1988), pp. 3-6. PLAZA ARQUÉ, Carme – “La Masó, un topònim de luxe”. Sis Focs 29 (1989), pp. 3-6. PONSIC, Pere – “Castellnou”. in Catalunya Romànica, XXV. El Vallespir, El Capcir, El Donasà, La Fenolleda, El Perapertusès. Barcelona, 1996. RUNCIMAN, Steven – Vísperas sicilianas: una historia del mundo mediterráneo a finales del siglo XIII. Madrid: Alianza Ed., 1979. SANS I TRAVÉ, Josep M. – “Alguns aspectes de l'establiment dels templers a Catalunya: Barberà”. Quaderns d'Història Tarraconense 1 (1977), pp. 9-59. SANS I TRAVÉ, Josep M. – “El Rourell, una preceptoria del Temple al Camp de Tarragona (1162?-1248) ”.  Butlletí Arqueològic 133-140 (1977), pp. 133-201. SANS I TRAVÉ, Josep M. – “Pere de Queralt, primer feudatari de l'Espluga de Francolí (1150-1166)”. in Universitas Tarraconensis. Revista de Geografia, Història i Filosofia 2 (1977-1978), pp. 25-52. SANS I TRAVÉ, Josep M. – “La comanda de Vallfogona de Riucorb. Primera part: la creació i formació del patrimoni (segles XII i XIII)”. Quaderns d'Història Tarraconense 2 (1980), pp. 7-54. SANS I TRAVÉ, Josep M. –  "La introducció de l'orde del Temple a Catalunya i la seva organització". in Actes de les Primeres Jornades sobre els Ordes Religioso-Militars als Països Catalans (segles XII-XIX). Tarragona: Diputació de Tarragona, 1994, pp. 17-42. SANS I TRAVÉ, Josep M. – Fra Arnau de Torroja, Mestre del Temple a Catalunya (1166-1181) i Mestre Major de l’Orde (1181-30 de setembre de 1184). Barcelona: Reial Acadèmia de Bones Lletres de Barcelona, 2006, pp. 12-130. SCHENK, Jochen G. – “Forms of lay association with the Order of the Temple”. Journal of Medieval History 34 (2008), pp. 79-103. SCHENK, Jochen G. – Templar families. Cambridge: Cambridge University Press, 2015. SEGURA VALLS, Joan– Historia de la villa de Santa Coloma de Queralt. Barcelona: Imprenta Vicente Magriñá, 1879. SEGURA VALLS, Joan – “Aplech de documents curiosos e inèdits fahents per la Història de las costums de Catalunya”. in Jochs Florals de Barcelona. Barcelona: Estampa de la Renaixensa, 1883. SEGURA VALLS, Joan – “Repàs d’un Manual notarial del temps del rey En Jaume I”. in Congrés [Ier] d’Història de la Corona d’Aragó, dedicat al Rey en Jaume I y a la seua època. I, Barcelona: Stampa d’en Francisco Altés, 1909, pp. 300-326. SEGURA VALLS, Joan – Història de Santa Coloma de Queralt. Refosa i ordenada en la seva ampliació per Joaquim Segura Lamich. 2ª ed. Santa Coloma de Queralt, 1971. SELWOOD, Dominic – Knights of the Cloister. Woodbridge: The Boydell Press, 1999. SOBREQUÉS VIDAL, Santiago – Els barons de Catalunya. 3ª ed., Barcelona: Editorial Vicens Vives, 1970. TOMMASI, Francesco – “Uomini e done negli ordini militari di Terrasanta. Per il problema delle case doppie e miste negli ordini giovanita, templare e teutonico (secc. XII-XIV)”. in elm, Kaspar; Parisse, Michel (eds.) – Doppelklöster und andere Formen der Symbiose männlicher und weiblicher Religiosen im Mittelalter. Berlin: Duncker et Humblot, 1992. (Berliner Historische Studien, Band 18, Ordensstudien VIII), pp. 177-202. TORMO y MONZÓ, Elias – “Dictamen de Santa María de Bell-lloch en Santa Coloma de Queralt (Tarragona)”. Boletín Arqueológico año XLIV, época IV, fasc. 3-4  (1944), pp. 58-66. TORRES, Miquel y SANFELIU, Guiu – “Entre el Corb i l’Ondara. Relacions entre nobles i templers: els Anglesola, els Cervera i els Timor-Queralt”. Actes de la XXXVII Jornada de Treball. Barbens: Grup de Recerques de les Terres de Ponent,  2008, pp. 90-108. VILAGINÉS SEGURA, Jaume – “Pere de Rovira, un templer del Vallès”. Notes 20  (2005), pp. 43-60.